Exploring multi-level factors determining social participation of students with intellectual disabilities in inclusive physical education classes - Christoffer Klenk; Matthias Buser (Current Issues in Sport Science)
Introduction The UN CRPD aims at effective participation of students with disabilities (SwD) in education (Art. 24). Reality of inclusive physical education (IPE) is different, however. In specific, social participation (SP) – a construct comprising of contacts, friendships, self-perception and acceptance (Koster et al., 2009) – has yet not been accomplished. Schluchter et al. (2024), observed that students with intellectual disabilities (SwID) show lower levels of SP, with fewer friendships, less engagement in social interactions and reduced peer acceptance compared to their non-disabled classmates. Apparently, the potential of sport for promoting SP is not a self-mechanism but is determined by factors at the individual level (e.g., athletic ability) and the class level (e.g., teachers’ competences, class climate). Although there is lively research on SP in educational contextes, the state of research lacks studies specific on IPE and determining factors. To fill this gap, this study analyses SP of SwID in IPE and its relevant factors at student and class level.